Strengthening Governance and Institutional Capacity at the Nutrition-Food Supply Policy Nexus; Comment on "What Opportunities Exist for Making the Food Supply Nutrition Friendly? A Policy Space Analysis in Mexico" - Sirinya Phulkerd (Kerman University of Medical Sciences, 2022)
Cervantes et al have provided an insightful addition to the policy literature by identifying the contextual, political, and policy factors that create constraints and opportunities for putting nutrition at the center of the food supply chain policy process. This commentary discusses important elements and features when aiming for reconciling nutrition goals and food supply policy, provides some examples of the salience of nutrition of non-health policies in countries with different income levels, and argues for improving governance for better nutrition outcomes and inspiring institutional interest and idea of food supply policy actors around population nutrition. Cervantes et al highlight the political context that favors nutrition outcomes, nutrition advocacy in the public agenda, and multisectoral mechanisms which can keep the nutrition objective moving forward in the food supply sector. However, a wider view on governance and institutional capacity is needed, recognizing government action by multiple sectors, with diverse sets of actors. The expanded understanding of nutrition, which includes considering nutrition as an emerging facet of food systems, by policy actors is needed. Enhancing discourse involving nutrition and food supply actors is important in order to appeal to the wider public and opinion leaders across the political spectrum. Accomplishing this also requires political will and an advocacy movement, especially by civil society and grassroots movements.